Priorities in the Modern Organization of University Science in the Light of the Principal-Agent Theory - D. G. Sandler; V. A. Koksharov; V. V. Kruzhaev; A. Р. Bagirova (Высшее образование в России)
The article focuses on the current state of the balance of interests in the field of organizing research activities in Russian universities. The theoretical framework of the research is the theory of the principal-agent, from the position of which the research management system is considered through the relationship between actors who have different degrees of awareness and potentially actin different interests. The purpose of the study is to compare the problems in the field of organizing funding, digitalization and scientific cooperation, which were the most important for agents, with those strategic decisions that took place at the level of the principal after extensive expert discussions. The following sources were used: 1) the results of the largest expert project implemented at the initiative of the Ministry of Science and Higher Education of the Russian Federation; 2) the results of a sociological study conducted at the Ural Federal University, where scientists and employees involved in the organization of scientific research were interviewed. A limitation of the study was the difficulty of comparing the results of the qualitative analysis made by the principal and the quantitative assessments given by the agents. In this connection, an emphasis in the interpretation of the results was made not so much on the specific quantitative assessments of the agents as on the comparison of the priorities of the problems expressed by the agents and the solutions generated by the principal. The results of the analysis showed that most of the priority tasks for agents in the field of organizing financing, digitalization, scientific cooperation were reflected in the decisions of the principal. The gaps stem from the lack of solutions aimed at intensifying research work in terms of monitoring the current scientific thematic agenda, and the importance of increasing the weight of this criterion when evaluating scientific projects. There are two ways to reduce the identified gaps: 1) inclusion of the support for the development of aggregators that allow scientists to quickly obtain the most relevant results with growing volumes of data into the list of tasks facing the principal; 2) development of modern analytical information and digital mechanisms for assessing the prospects of topics, which creates conditions for their compliance with the dynamic global research agenda.